The Effect of EGFR DNA Methylation on the Incident of Endometriosis - Anisah Nida'ul Haq; Ocktariyana Ocktariyana; Zen Hafy; Irsan Saleh (Sriwijaya Journal of Medicine, 2024)
Endometriosis is a gynecological condition characterized by the development of endometrial tissue outside the uterus, often leading to pain and infertility. We explore the relationship between endometriosis and the effects of DNA methylation on the Epidermal Growth Factor Receptor (EGFR) gene. DNA methylation, an epigenetic mechanism, involves adding a methyl group to cytosine bases followed by guanine in CpG islands, thereby influencing gene expression through hypermethylation or hypomethylation. In endometriosis, methylation patterns on specific genes can lead to transcriptional changes, impacting inflammatory processes and hormonal functions, such as estrogen, that support the growth of ectopic tissue. Variations in the EGFR gene's DNA methylation are linked to elevated cellular activity and expression, which aids in the pathophysiology of endometriosis. These findings highlight the potential of DNA methylation as a therapeutic target in treating endometriosis, offering hope for improved patient outcomes.